Varied Institutional Responses to COVID-19: An Investigation of U.S. Colleges' and Universities' Reopening Plans for Fall 2020 - Tyler D. Blanco; Brian Floyd; Bruce E. Mitchell II; Rodney P. Hughes (SAGE Publishing, 2022)
The authors investigate coronavirus disease 2019 (COVID-19) risk factors, suitability of online instruction, politics, and institutions' finances as rationales guiding instructional delivery decisions for fall 2020, after COVID-19's emergence. Contributions include estimating multinomial logit regressions with mode of delivery as a categorical variable, integrating resource dependence and crisis response as theoretical frames, and introducing new predictor variables, including a measure of local residential access to broadband Internet. Findings suggest that county populations, local political preferences, and the percentage of revenue derived from auxiliary enterprises were consistent predictors of delivery mode. Political parties of an institution's governor and congressional representative were predictive of delivery mode for institutions in the lowest tercile of endowment per student but not for institutions in the highest tercile. Bottom-tercile institutions substituted from online to in-person reopening as reliance on revenue from auxiliary enterprises increased, but top-tercile institutions appeared only to substitute from hybrid to in-person or from online to hybrid delivery as revenue from auxiliary enterprises or tuition and fees increased.